Information technologies and provision of national identification cards by the Bolivian Police: Evidence from two randomized natural fields experiments - Alberto Chong; Gustavo Machicado Salas; Monica Yanez-Pagans (Institute for Advanced Development Studies (INESAD), 2014)
This paper investigates the potential of information technologies to improve public service delivery and empower citizens in the context of two unusual randomized natural experiments occurring within one particular bureaucratic process: the renewal of a national identification card by the Bolivian Police. The first experiment arises from the random assignment of both police officers and applicants to a manual or digital renewal process, which is identical in all aspects except that the digital renewal process makes use of information technologies as part of the renewal process. The second experiment arises by the existence of technical failures within the digital renewal process, which allows police officers to change from the digital to the manual renewal process randomly across renewal day. The efficiency of public service delivery is measured in terms of both renewal success rates (which average to a strikingly low rate of 72 percent in our sample) and time-it-takes to renew an identification card. The causal effect of information technologies on public service delivery is estimated using two different identification strategies. In the first one, applicant-police officer pairs randomly assigned to each one of these two renewal processes are compared after controlling for renewal day fixed effects. In the second one, applicant-police officer pairs randomly assigned to the digital process are compared to those randomly assigned to this same process but who experienced a technical failure within the process, which allows to directly control for unobserved heterogeneity at the police officer level. We find that information technologies significantly improve the quality of public service delivery. Applicants randomly assigned to the digital renewal process are on average 12 percentage points more likely to complete the renewal process as compared to those randomly assigned to the manual one. Further, successful applicants randomly assigned to the digital process take on average 31 percent less time to complete the process as compared to those randomly assigned to the manual one. Lastly, we find that information technologies significantly lower barriers in access to national identification cards by promoting a more equitable provision across the population. We discuss several channels through which technologies might be improving efficiency and promoting equity within this particular bureaucratic process. Overall, our findings suggest that information technologies might be achieving these goals by introducing efficiencies (such as reducing administrative shortcomings and transaction costs), and limiting the exercise of discretion by police officers within the renewal process.
Keywords: C93; O38; J24; 330